1999
DOI: 10.1080/00224549909598358
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Overqualification and Health: A Longitudinal Analysis

Abstract: The authors examined the effects of perceived overqualification on health and health decline by means of a 2-wave panel study of members of a midwestern American Postal Workers Union local. The 1st hypothesis was that overqualification was negatively related to health at Time 2 (T2); the second hypothesis was that overqualification was positively related to perceived health decline at T2. Neither was supported by the data. However, the relationships were in the expected direction for perceived mismatch but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 36 publications
0
22
0
7
Order By: Relevance
“…The results of the rather limited number of studies which have investigated the health risks of overeducation are conflicting (Bracke et al . , Friedland and Price , Johnson and Johnson , , , Peter et al . , Scott‐Marshall et al .…”
Section: Introductionmentioning
confidence: 99%
“…The results of the rather limited number of studies which have investigated the health risks of overeducation are conflicting (Bracke et al . , Friedland and Price , Johnson and Johnson , , , Peter et al . , Scott‐Marshall et al .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other researchers use relative discrepancies in material goods or income to predict income satisfaction (Crawford Solberg, Diener, Wirtz, Lucas, & Oishi, 2002;G. Johnson & Johnson, 1999).…”
mentioning
confidence: 99%
“…Some have shown that overqualified and overeducated workers were more likely to experience poor or declining self-rated health compared to workers appropriately matched to their jobs (Friedland & Price, 2003; Johnson & Johnson, 1996, 1997, 1999; Smith & Frank, 2005). Overqualified and overeducated workers also had higher rates of adverse mental health outcomes, including depression, anxiety, and psychological distress (Friedland & Price, 2003; Gal, Kaplan, Gross, & Levav, 2008; Johnson & Johnson, 1996, 1997, 1999; Lundeberg et al, 2009; O’Brien & Feather, 1990). Some evidence also suggests more negative physical health outcomes among overeducated workers, including higher risk of ischemic heart disease (Peter et al, 2007) and low-birth weight deliveries (Meyer, Warren, & Reisine, 2010), than among workers with expected levels of education for their jobs.…”
Section: Relevance For Healthmentioning
confidence: 99%
“…The health consequences of these phenomena for immigrant workers have largely been unexplored. Some evidence indicates that overeducation and overqualification are associated with adverse health effects, including poor self-rated health, depression, anxiety, and ischemic heart disease, among the general working population (Friedland & Price, 2003; Johnson & Johnson, 1996, 1997, 1999; Lundberg, Kristenson, & Starrin, 2009; Peter, Gassler, & Geyer, 2007; Smith & Frank, 2005). …”
mentioning
confidence: 99%